Double Hydrogen Bonding Dimerization Propensity of Aqueous Hydroxy Acids Investigated Using Vibrational Optical Activity - Kaminský, Jakub; Horáčková, Františka; Biačková, Nina; Hubáčková, Tereza; Socha, Ondřej; Kubelka, Jan (The journal of physical chemistry. B, 2021)
Lactic and malic acids are key substances in a number of biochemical processes in living cells and are also utilized in industry. Vibrational spectroscopy represents an efficient and sensitive way to study their structure and interactions. Since water is the natural environment, proper understanding of their molecular dynamics in aqueous solutions is of critical importance. To this end, we employed Raman spectroscopy and Raman optical activity (ROA) to study the conformation of l-lactic and l-malic acids in water (while varying pH, temperature, and concentration), with special emphasis on their double hydrogen bonding dimerization propensity. Raman and ROA experimental data were supported by extensive theoretical calculations of the vibrational properties and by additional experiments (IR absorption, vibrational circular dichroism, and NMR). Conformational behavior of the acids in water was described by molecular dynamics simulations. Reliability of the results was verified by calculating the vibrational properties of populated conformers and by comparing thus obtained spectral features with the experimental data. Calculations estimated the incidence of H-bonded dimers in water to be low in lactic acid and comparable to monomers in malic acid. The "hybrid" approach presented here reveals limitations of relying on the experimental spectra alone to study dimer formation.
Keywords: reprodukovatelnost výsledků; dimerizace; Hydrogen Bonding; hydroxykyseliny; Ramanova spektroskopie; vodíková vazba; Spectrum Analysis, Raman; Water; Dimerization; Hydroxy Acids; Reproducibility of Results; optická otáčivost; Optical Rotation; Vibration; voda; vibrace